The role of miR-154 in early lung development - Kolck, Johannes; Justus Liebig University Giessen (My University, 2019)
Since the discovery of the first regulatory RNA strands in 1993, the number of known micro RNAs has steadily increased. However, the function of the individual molecules is often unknown. The aim of our study was to investigate the role of microRNA 154 in embryonic lung development. Our strategy included two opposing experimental approaches: A "gain of function" and a "loss of function" experiment. In both approaches, we analyzed the lung morphology and the changes at the genetic level. For the gain of function approach, we designed a mouse line that overexpressed miR-154 in the pulmonary epithelium upon doxycycline food application. We induced this process from embryonic day 7.5 until organ harvest (at E18.5). Using quantitative PCR we were able to prove the successful overexpression. As a consequence of epithelial miR-154 overexpression a phenotype with thinned alveolar septa and elongated sacculi was observed microscopically. In alveolar morphometry we found a significant reduction of septal thickness (in micrometer) and a significant increase of airspace. The parameter for volume-to-surface ratio (MLI) was also increased. Searching for the genetic correlate for this phenotype, we focused on four gene groups related to lung development: The signal cascades of the cytokines Fgf10 and Tgf-ß, as well as the marker genes for epithelial cells and alveolar myofibroblasts (AMF). AMFs are important mediators of alveolar separation. In our analysis, their marker genes showed a significant down regulation. However, the subsequent Acta2 staining did not reveal any difference in AMF presence.For the loss of function approach, we blocked miR-154 with a morpholino solution. We explanted embryonic lungs at E11.5 and cultivated the organs in vitro for 72 hours. Morphologically, the lungs of the experimental group showed a significantly reduced formation of lung buds. Gene analysis of Fgf10 and Tgf-beta signaling, but also the gene markers of epithelial cells and AMFs showed a trend towards overexpression.

Seit der Entdeckung der ersten regulatorischen RNA-Stränge im Jahr 1993 nimmt die Anzahl bekannter Micro-RNAs stetig zu. Die Funktion der einzelnen Moleküle ist jedoch häufig unbekannt. Ziel unserer Studie war es die Rolle der microRNA 154 in der frühen embryonalen Lungenentwicklung herauszuarbeiten. Unsere Strategie dabei umfasste zwei gegensätzliche experimentelle Herangehensweisen: Ein Gain - und ein Loss of function Experiment. In beiden Ansätzen analysierten wir die Morphologie der Lungen und die Veränderungen auf genetischer Ebene.Für den Gain of function Ansatz designten wir eine Mauslinie, die miR-154 bei Applikation von Doxycyclin-Nahrung im Lungenepithel überexpremierte. Wir induzierten diesen Prozess von Embryonaltag 7.5 bis zur Organentnahme (E18.5). Mittels quantitativer PCR konnten wir die erfolgreiche Überexpression beweisen. Als Folge der epithelialen miR-154 Überexpression zeigte sich mikroskopisch ein Phänotyp mit verdünnten Alveolarsepten und elongierten Sacculi. Passend dazu fanden wir in der Alveolarmorphometrie signifikant verschmälerte alveoläre Septen (in Micrometer) und einen signifikant erhöhten Anteil an Luft im Gewebe. Auch der Parameter für das Volumen-Oberflächen-Verhältnis (MLI) war erhöht. Auf der Suche nach dem genetischen Korrelat für den vorliegenden Phänotypen fokussierten wir vier Gengruppen, die im Zusammenhang mit der Lungenentwicklung stehen: Die Signalkaskaden der Zytokine Fgf10 und Tgf-ß, sowie die Markergene für Epithelzellen und Alveolarmyofibroblasten (AMF). AMFs sind als wichtige Mediatoren der Alveolarseparation bekannt. Die Expression dieser Genmarker war in unserer Analyse signifikant reduziert. Die anschließenden Acta2 Färbungen unterschieden sich jedoch nicht hinsichtlich der Anwesenheit der AMFs.Für den Loss of function Ansatz blockierten wir die miR-154 mit einer Morpholino-Lösung. Dazu explantierten wir embryonale Lungen an E11.5 und kultivierten die Organe für 72 Stunden in-vitro. Morphologisch zeigten die Lungen der Experimentalgruppe eine signifikant verminderte Ausbildung von Lungenknospen. Die Genanalyse des Fgf10 und Tgf-beta Signaling, aber auch die Genmarker der Epithelzellen und AMFs zeigte einen Trend zur Überexpression.
Keywords: ddc:610